Correction: Trypanosoma brucei CYP51: Essentiality and Targeting Therapy in an Experimental Model. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005125.].